Label-Free Fluorometric Detection of Adulterant Malachite Green Using Carbon Dots Derived from the Medicinal Plant Source Ocimum tenuiflorum - Shukla D.; Pandey F.P.; Kumari P.; Basu N.; Tiwari M.K.; Lahiri J.; Kharwar R.N.; Parmar A.S. (My University, 2025)
Food adulteration is an alarming concern in developing countries causing an increased rate of cancer incidents. This study aims to address this concern by detecting adulteration in green vegetables. A facile green one-step and cost-effective strategy to synthesize carbon quantum dots derived from a herbal source has been utilized to design a fluorescence-based sensor for detecting malachite green (MG), a toxic carcinogenic dye, commonly used as an adulterant to give a fresh green look to green vegetables. The leaf-extract of Ocimum tenuiflorum has been used to synthesize highly photostable carbon dots for detecting MG with a limit of detection (LOD) as low as 18 nM. Further, this principle has been utilized to design a prototype calorimetric sensor. The mechanism of the interaction between malachite green and carbon dots has been probed using DFT by employing the SMD solvation model. In addition, CQDs also possess strong antioxidant activity and minimal cytotoxicity enabling their utilization in many biological and sensing applications. This shows the versatility of these easily scalable carbon dots. © 2019 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim